A little Step. Volume 1 - Szeto, Mimi (Nakama Press, 2025)
"Lau Yu Kiu, A fifth-year student, had always dreamed of studying at a foreign art university. However, because she feared others' critiques of her work, she couldn't find it within herself to submit any of her creations. One day, while Yu Kiu was in the art room, she heard a beautiful guitar sound from downstairs. It turned out to be played by Lee Hou Yuet, a classmate with a questionable reputation..." --